Molecular breakdown: a comprehensive view of anaplastic lymphoma kinase (ALK)‐rearranged non‐small cell lung cancer. Issue 3 (28th September 2017) - Noh, Ka‐Won; Lee, Mi‐Sook; Lee, Seung Eun; Song, Ji‐Young; Shin, Hyun‐Tae; Kim, Yu Jin; Oh, Doo Yi; Jung, Kyungsoo; Sung, Minjung; Kim, Mingi; An, Sungbin; Han, Joungho; et al.
Abstract: Most anaplastic lymphoma kinase ( ALK )‐rearranged non‐small cell lung cancers (NSCLCs) show good clinical response to ALK inhibitors. However, some ALK ‐rearranged NSCLC patients show various primary responses with unknown reasons. Previous studies focused on the clinical aspects of ALK fusions in small cohorts, or were conducted in vitro and/or in vivo to investigate the function of ALK. One of the suggested theories describes how echinoderm microtubule‐associated protein‐like 4 ( EML4 ) –ALK variants play a role towards different sensitivities in ALK inhibitors. Until now, there has been no integrated comprehensive study that dissects ALK at the molecular level in a large scale. Here, we report the largest extensive molecular analysis of 158 ALK ‐rearranged NSCLCs and have investigated these findings in a cell line construct experiment. We discovered that NSCLCs with EML4–ALK short forms (variant 3/others) had more advanced stage and frequent metastases than cases with the long forms (variant 1/others) ( p = 0.057, p < 0.05). In vitro experiments revealed that EML4–ALK short forms show lower sensitivity to ALK inhibitors than do long forms. Clinical analysis also showed a trend for the short forms showing worse PFS. Interestingly, we found that breakpoints of ALK are evenly distributed mainly in intron 19 and almost all of them undergo a non‐homologous end‐joining repair to generate ALK fusions. We also discovered four novel somatic ALK mutations in NSCLC (T1151R, R1192P, A1280V, and L1535Q) that confer primary resistance; all of them showed strong resistance to ALK inhibitors, as G1202R does. Through targeted deep sequencing, we discovered three novel ALK fusion partners ( GCC2, LMO7, and PHACTR1 ), and different ALK fusion partners showed different intracellular localization. With our findings that the EML4–ALK variants, new ALK somatic mutations, and novel ALK ‐fusion partners may affect sensitivity to ALK inhibitors, we stress the importance of targeted therapy to take the ALK molecular profiling into consideration. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.